Influence of Post-Weld Heat Treatment on the Performance of UHSS Joints - Tumer, Mustafa; Kisasoz, Alptekin; Pixner, Florian; Enzinger, Norbert (MDPI, 2025)
Ultra-high strength steel (UHSS) contributes significantly to lightweight design, environmental compatibility and lower fuel consumption. However, it is essential to maintain excellent mechanical properties in terms of structural integrity, strength and ductility after the applied welding process. In this study, the effect of post-welding heat treatments on the welding of UHSS S1100MC was investigated in order to compensate for the deterioration in toughness that occurred as a result of joining by electron beam welding. Electron beam welding (EBW) provides high energy density and therefore relatively low heat input compared to arc welding. However, the narrow fusion zone (FZ) and heat-affected zone (HAZ) may have insufficient toughness values due to rapid cooling of the joint. In order to protect the relationship between strength and toughness, both the material and the joint were subjected to heat treatment at 500, 650 and 750 degrees C temperatures for 2 h and were cooled in the furnace. Microstructural characterization and mechanical testing, namely hardness, Charpy impact and tensile tests, were performed to correlate the influence of post-weld heat treatment on the microstructural formation and the corresponding mechanical properties. While the material and the joint maintained their hardness values at 500 degrees C of around 412 +/- 15 HV0.2, there was an approximately 8% decrease in hardness to 378 +/- 18 HV0.2 at 650 degrees C. At 750 degrees C, it dramatically lost its high hardness properties, resulting in a low 178 +/- 9 HV0.2. However, direct quenching from the austenitic temperature resulted in fresh martensite, which provided both the required strength and toughness values in the EBW joint. With a hardness of 437 HV0.2, a tensile strength of 1345 MPa and a fracture elongation of more than 9%, superior mechanical properties could be achieved.
Keywords: EBW; UHSS; microstructure; hardness; toughness; STRENGTH-TOUGHNESS; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics